Fine needle aspiration cytology of laryngeal lesions: an experience from tertiary cancer care center - Mukundapai, Malathi; Patil, Akkamahadevi; Nargund, Ashwini; Biswas, Siddhartha; Sethumadhavan, T.; Kapali, Anuradha; Chavan, Purushottam (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Squamous Cell Carcinoma (SCC) comprises about 95% of laryngeal malignancies. Translaryngeal Fine Needle Aspiration Cytology (TLFNAC) of endolaryngeal and hypopharyngeal malignancies helps in early diagnosis. Although the diagnosis of a malignancy is often self-evident to a clinician, a tissue diagnosis is a must for starting treatment. TLFNAC helps the clinicians to plan the management at the earliest. Hence this study is to evaluate the utility of percutaneous translaryngeal FNAC in diagnosis of laryngeal lesions. Methods: 189 Cases of Translaryngeal FNACs done during the period of Jan 2014 to Dec. 2015 were retrieved from the cytology register. FNAC was always done after Head and Neck radiology image studies. Usual FNA procedure was followed. FNA done with or without guidance and at times with clinician’s assistance. Smears stained with MGG and Pap stain, and cytomorphological diagnosis was made. Results: Out of 189 cases, aspirates were satisfactory in 146 cases and unsatisfactory in 43 cases. Of the 146 cases, 122 were SCC, pleomorphic adenoma one case, adenoid cystic carcinoma one case, 8 were uncategorized neoplasms and one case was granulomatous inflammation and remaining 14 cases had nonspecific findings. Conclusions: TLFNA is simple, cost effective, less invasive and safe as compared to DL biopsy with less turnaround time for laryngo-pharyngeal lesions. This reduces the number of visits to OT and helps the clinicians in planning the treatment early like RT/CT or surgery. This avoids tracheostomy in borderline airway obstruction cases.